ORGANIZATIONAL AND METHODOLOGICAL FEATURES OF TRAINING TABLE TENNIS PLAYERS 10-12 YEARS OLD (British Journal of Global Ecology and Sustainable Development, 2023)
This article, presented by the author, highlights the features of the preparation of table tennis players 10-12 years old. Instructions were also given regarding the development of physical, as well as technical and tactical actions of young table tennis players.